Association of Caesarean Uterine Scar Health in Women with Previous One Caesarean Section in Relation to Inter- Pregnancy Interval - Humera Rani, Shazia Rafique, Noreen Majeed, Ayesha Irfan, Humera Rani, Shazia Rafique, Noreen Majeed, Ayesha Irfan (Journal of Rawalpindi Medical College, 2019)
Background:To find out safe inter pregnancy interval in patients with previous one caesarean section and promote trial of labour after caesarean (TOLAC) . Methods: In this descriptive study one hundred and fifty patients with singleton pregnancy and previous one caesarean section, who were planned for elective caesarean section, between 37-40 weeks, were included. Patients with multiple pregnancies, ruptured uterus, failure of TOLAC, multiple caesarean sections and preterm pregnancies were excluded. Visual uterine scar health was assessed per operatively in relation to different inter pregnancy intervals. Scar health was categorized as healthy or thick, thin, transparent and partial dehiscence. . Result:Patients, with inter- pregnancy interval of 12-18 months, had a high (69.6%) healthy scar. In patients with inter-pregnancy interval of 19-24 months, 76.9% scars were healthy. The group of patients whose inter pregnancy interval was more than 24 months, 71.8% scar were healthy Conclusion: When intra operative visual scar health was assessed in relation with inter pregnancy interval. No significant difference was found in uterine scar health in different inter pregnancy intervals.